Field notes contributed by Thomas H. Kent, spring 1979 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1979)
Spring report of birds and various locations contributed by Thomas H. Kent. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1979. Epson - sheet feed/flatbed